A Review of the Efficacy and Side Effects of COVID-19 Vaccines - Neyazi, Abdul Jawid (Journal of Natural Sciences – Kabul University, 2022)
COVID-19 emerged in December 2019 in Wuhan, China. Since the outbreak of this disease, various countries worldwide have strived to develop effective vaccines to prevent its spread and make them accessible to the public. Among these, seven vaccines have been approved by the World Health Organization: Pfizer-BioNTech, Moderna, Johnson & Johnson, AstraZeneca, Sinopharm, Sinovac, and Covishield. Pfizer and Moderna vaccines demonstrated the highest efficacy, with rates of 95% and 94.5%, respectively, while Covishield and Sinovac showed the lowest efficacy, at 62% and 51%, respectively. Among these vaccines, the Johnson & Johnson vaccine was associated with severe side effects, including cerebral venous sinus thrombosis and blood clotting accompanied by reduced thrombocyte levels.